Engineered, axially-vascularized osteogenic grafts from human adipose-derived cells to treat avascular necrosis of bone in a rat model. (November 2017) - Ismail, Tarek; Osinga, Rik; Todorov, Atanas; Haumer, Alexander; Tchang, Laurent A.; Epple, Christian; Allafi, Nima; Menzi, Nadia; Largo, René D.; Kaempfen, Alexandre; Martin, Ivan; Schaefer, Dirk J.; et al.
Graphical abstract: Abstract: Background: Avascular necrosis of bone (AVN) leads to sclerosis and collapse of bone and joints. The standard of care, vascularized bone grafts, is limited by donor site morbidity and restricted availability. The aim of this study was to generate and test engineered, axially vascularized SVF cells-based bone substitutes in a rat model of AVN. Methods: SVF cells were isolated from lipoaspirates and cultured onto porous hydroxyapatite scaffolds within a perfusion-based bioreactor system for 5 days. The resulting constructs were inserted into devitalized bone cylinders mimicking AVN-affected bone. A ligated vascular bundle was inserted upon subcutaneous implantation of constructs in nude rats. After 1 and 8 weeks in vivo, bone formation and vascularization were analyzed. Results: Newly-formed bone was found in 80% of SVF-seeded scaffolds after 8 weeks but not in unseeded controls. Human ALU + cells in the bone structures evidenced a direct contribution of SVF cells to bone formation. A higher density of regenerative, M2 macrophages was observed in SVF-seeded constructs. In both experimental groups, devitalized bone was revitalized by vascularized tissue after 8 weeks. Conclusion: SVF cells-based osteogenic constructs revitalized fully necrotic bone in a challenging AVN rat model of clinically-relevant size. SVF cells contributed to accelerated initial vascularization, to bone formation and to recruitment of pro-regenerative endogenous cells. Statement of significance: Avascular necrosis (AVN) of bone often requires surgical treatment with autologous bone grafts, which is surgically demanding and restricted by significant donor site morbidity and limited availability. This paper describes a de novo engineered axially-vascularized bone graft substitute and tests the potential to revitalize dead bone and provide efficient new bone formation in a rat model. The engineering of an osteogenic/vasculogenic construct of clinically-relevant size with stromal vascular fraction of human adipose, combined to an arteriovenous bundle is described. This construct revitalized and generated new bone tissue. This successful approach proposes a novel paradigm in the treatment of AVN, in which an engineered, vascularized osteogenic graft would be used as a germ to revitalize large volumes of necrotic bone.